Optimizing Tissue Culture for Yellow Dragon Fruit (Selenicereus megalanthus) Propagation: Enhancing Shoot and Root Induction - Dirga, Kate Tiffany; Maryuandini, Ufi; Sachio, Sachio; Sukma, Dewi (Journal of Tropical Crop Science, 2025)
Yellow dragon fruit (Selenicereus megalanthus) "Palora" variety is a tropical cactus recognized for its yellow pericarp, white mesocarp, and black seeds. Dragon fruits are also known as pitaya. The yellow pitaya variant is regarded as the sweetest and most nutrient-dense, with high commercial value among the commonly cultivated pitaya types. However, large-scale cultivation of yellow dragon fruit remains limited by propagation constraints. The conventional propagation method using vegetative stem cuttings is labour-intensive and results in inconsistent growth and genetic variability. Tissue culture has emerged as a viable biotechnological alternative, enabling rapid multiplication of genetically uniform and disease-free plantlets under controlled conditions. The study aimed to optimize tissue culture medium for enhancing shoot induction on yellow dragon fruit. The experiments were conducted in two steps. The first step evaluated the explant response in MS medium containing 3 mg.L-1 BAP and varying NAA concentrations (0.1, 0.2, 1, 2, and 3 mg.L-1). The results showed that an elevation in NAA concentration promoted progressive growth in shoots, roots, and callus. However, when NAA was further augmented to 3 mg.L-1, shoot and root formation were repressed, while callus formation increased. The second step evaluated the combined effects of auxin and cytokinin on shoot formation. A factorial treatment design was applied using combinations of three NAA concentrations (1, 2, and 3 mg.L-1) and three BAP concentrations (1, 2, and 3 mg.L-1), resulting in nine treatment combinations, with the lowest concentration (NAA 1 mg.L-1 + BAP 1 mg.L-1) as the control. Statistical analysis revealed that NAA, BAP, and their interaction had a significant effect on the number of shoots. The optimal treatment for producing the highest number of shoots is a combination of NAA at 3 mg.L-1 and BAP at 2 mg.L-1.